THE INFLUENCE OF CONCRETE COVER ON THE BEARING CAPACITY AND RELIABILITY OF THE REINFORCEMENT CONCRETE SLAB – COLUMN SYSTEM - Katarzyna Sieńkowska; Agata Tułecka; Lidia Buda-Ożóg (Journal of Civil Engineering, Environment and Architecture, 2021)
The reliability of building structures is a very important design criterion. The required level of security depends not only on the function and purpose of the facility, but also on the parameters considered at the design stage. There are factors to that with some probability they increase the uncertainty of the adopted parameters in the calculations, as a result of which the structure fails. It happens that execution errors are made during the process of creating an object. One of the significant disadvantages is the increase in the reinforcement cover thickness compared to the designed value, and hence the reduction of the effective depth of cross-section. The purpose of the analyzes presented in the article was to estimate the influence of the top reinforcement cover thickness on the reliability and bending and punching resistance in the reinforced concrete slab being part of the slab-column system. The reliability index βc was determined by the Cornell method. The analysis focused on a fragment of a cross reinforced slab, which is an element of the column-slab structure of a shopping mall. The ARSA 2019 program was used for the analysis of the structure. The impact of the coefficient of variation of the effective depth on the reliability index was also analyzed. The obtained values were compared with the target value of the reliability index read from EN 1990.